IPM strategy for the control of Bemisia tabaci (Hemiptera: Aleyrodidae) on melon and tomato - ESPINEL-C., CARLOS; LOZANO, MARÍA DENIS; VILLAMIZAR-R., LAURA; GRIJALBA-B., ERIKA; COTES-P., ALBA MARINA (Revista Colombiana de Entomología, 2008)
Bemisia tabaci is an economically important pest in melon and tomato crops. The Corpoica research center developed biopesticides for its control with promising results under laboratory conditions, leading to a need to evaluate them under field conditions. The objective of the present work was to evaluate a strategy of integrated pest management (IPM) on melon and tomato crops in El Espinal (Tolima) using a preformulation based on Paecilomyces fumosoroseus and a biopesticide based on Lecanicillium lecanii. Other components of insect management were integrated, such as yellow traps and pathogen management like soil solarization and the application of Trichoderma koningii. IPM plots (with biopesticides) were compared with a traditional farmer treatment. The presence of adults and immature stages were determined weekly and the total yield at harvest. Six applications of the biological products were carried out in melon and ten in tomato. Melon production in plots treated with L. lecanii was 29.4 t/ha, while in the plots treated with P. fumosoroseus and farmer treatment it was 27.3 t/ha and 25 t/ha, respectively. The highest production obtained in cherry tomato was in the treatment with P. fumosoroseus (14.7 t/ha), followed by L. lecanii treated plots (13.8 t/ha) and the farmer treatment (13.6 t/ha). These results suggest that the biological products based on the evaluated entomopathogens, introduced into a strategy of integrated crop management, are promising for B. tabaci control.